Do reservation wages react to regional unemployment? - Uwe Blien; Susanne Messmann; Mark Trappmann (European Regional Science Association (ERSA), 2012)
Reservation wages indicate the wage threshold for which individual workers are inclined to supply their working capacity. In important theoretical approaches it is assumed that this threshold depends on the unemployment rate. If this is true, the variation of reservation wages might be an important force behind the regional 'wage curve', which has been estimated in many empirical studies. Up to now, the connection to reservation wages has not been tested, since research are rather limited, since they depend on the availability of survey data. With the 'Labour Market and Social Security' study (PASS), a new large panel survey in Germany, information on re-gional reservation wages is available. PASS provides many variables usually expected to determine wages, such as gender, age, qualification etc. The data available therefore provides an excellent opportunity to test the relationship between unemployment and reservations wages. The analysis opens up the 'black box' of the wage generation process and delivers insights about its determining factors. J31, C20, R10 wage curve, reservation wage, regional labour markets
Keywords: 330